Pretrial In Indonesian Criminal Law - Supriyono, Supriyono; Arief Amrullah, M.; Gede Widhiana Suarda, I (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The law is a collection of rules that must be obeyed by all people in a society with the threat of having to compensate for losses or get criminal if they violate or ignore these rules, so that an orderly and fair life in that society can be achieved. The conception that embodies that Indonesia is a state of law basically has joints that are universal, such as the recognition and protection of human rights, the legality of the actions of the state or government in the sense of a legally accountable state apparatus, and the guarantee of Free Justice. The type of writing used by the author is juridical normative (legal research) juridical normative research is carried out by examining various rules of law that have a formal nature, namely laws, regulations and literature that contain theoretical concepts that are then connected to the problems that the author will discuss in this dissertation research. Pretrial as part of the criminal justice system in force in Indonesia is an effort to combat crimes that are penal by using criminal law as the main means of material criminal law and formal criminal law. Pretrial as part of law enforcement, as stated by Barda Nawawi Arief that the problem of law enforcement, both in abstracto and in concreto is an actual problem that has recently received a sharp spotlight from the public. As is the case with the implementation of pretrial which is part of a principle of the rule of law which is that a rule of law has various criteria and elements.Based on the foregoing, the philosophical basis of the pre-trial arrangement in Indonesian criminal law is based on the existence of human rights, namely because Indonesia is a state of law based on Pancasila and recognizes human rights. The idea of a pretrial institution was born from inspiration derived from Habeas Corpus in the Anglo Saxon judiciary, which provided a fundamental guarantee to the human being of the right to independence.